ANALISIS KESALAHAN EJAAN PADA BERITA POLITIK EDISI APRIL 2023 DALAM MEDIA MASSA DARING (DETIK.COM) - Khaerul Anwar; Samsul Bahri; Nana Triana Winata (Universitas Wiralodra, 2023)
This study analyzes and describes spelling errors in political news in the April 2023 edition of the Detik.com newspaper. The data in this study are spelling errors in the form of capital letters errors, word writing errors, italics errors, symbol writing errors. numbers, and punctuation errors. The objectives of this research include, among others, (1) knowing the types of spelling errors that exist in political news in the April 2023 edition of the Detik.com mass media and (2) analyzing and describing the forms of errors in the April 2023 edition of the Detik.com mass media. This research is a descriptive qualitative research with the subject of finding, analyzing, and describing data in the form of spelling errors. According to (Sugiyono, 2022) says that,